2017
DOI: 10.1177/1069397116685783
|View full text |Cite
|
Sign up to set email alerts
|

What Are Our Personal Memories for? Effects of Gender and Country in Perceived Functions of Everyday Memories in Danish and Spanish College Students

Abstract: Theorists in autobiographical memory (AM) studies generally agree that AMs serve three kinds of broad functions: self-related, social, and directive functions. Although these kinds of functions are probably universal, gender and country variations are expected. The study investigates perceived use of AMs in everyday life. Male and female Danish and Spanish college students were asked to carry a diary and report a sample of naturally occurring instances of AMs. Participants were asked to assess their memories i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Using the Reminiscence Function Scale (RFS; Webster, 1993 ), he identified that women's narratives contained greater number of specific memories than did men's narratives, and women scored higher on problem-solving RFS factor. This RFS factor could be considered as a doppelganger of the directive function of AM (Webster, 1993 ; Webster and McCall, 1999 ; Santamaría et al, 2017 ). It seems that women are less confident about their decisions and express more doubts about their behavior (Bengtsson et al, 2005 ; Robinson and Stubberud, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Reminiscence Function Scale (RFS; Webster, 1993 ), he identified that women's narratives contained greater number of specific memories than did men's narratives, and women scored higher on problem-solving RFS factor. This RFS factor could be considered as a doppelganger of the directive function of AM (Webster, 1993 ; Webster and McCall, 1999 ; Santamaría et al, 2017 ). It seems that women are less confident about their decisions and express more doubts about their behavior (Bengtsson et al, 2005 ; Robinson and Stubberud, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking the point that autobiographical memory has been posited to serve three fundamental functions: self, social, and directive (Bluck, Alea, Habermas, & Rubin, 2005), some researchers have claimed that the “Western” highly elaborative maternal style assists the manifestation of self‐function of autobiographical memories whereas the “Eastern” low elaborative maternal style supports social and directive functions (Alea & Wang, 2015; Santamaría, de la Mata, Cubero, & Hansen, 2017; Wang, 2013). As the repertoire of autobiographical memory function was recently enhanced by a function of emotion regulation (Kulkofsky, Wang, & Koh, 2009), there is no consensus on whether it is more suitable for the “Western” or “Eastern” type of personality.…”
Section: Cross‐cultural Diversity In Autobiographical Memorymentioning
confidence: 99%
“…The first subline can be referred to as self-construction in cultural settings. It includes studies about autobiographical memory, self, and culture (de la Mata, Santamaría, & Ruiz, 2016;Santamaría, de la Mata, Cubero, & Hansen, 2017;Santamaría, de la Mata, Hansen, & Ruiz, 2010), and about self-(re)construction in individuals and groups at risk of social exclusion (de la Mata, Cubero, Santamaría, & Saavedra, 2015;Saavedra, Cubero, & Crawford, 2012;Sala & de la Mata, 2017). These studies show an integration of concepts from cultural psychology to crosscultural research and eco-cultural approaches.…”
Section: ) Identity Construction In (Other) Sociocultural Settingsmentioning
confidence: 99%